Krisis Pencemaran Minyak Hitam [Sludge Oil] Merugikan Masyarakat Kepulauan: Bukti Dari Pulau Bintan. - Suyito Suyito; Haji Mustakim; Yessy Alvianti Dev; Linayati Lestari; Alpino Susanto (eScience Humanity Journal, 2025)
A study on the black oil pollution crisis [Sludge Oil] is detrimental to the island community, a proof from the island of Bintan that occurs and continues every year. This study contributes to a deep understanding that the black oil pollution crisis [Sludge Oil] in Bintan is not a trouble, but has become an issue in the theoretical context. So this is not just a regional problem, but has concerned a national issue about this black oil waste crisis. This study focuses on an argument question: "How does the Black oil pollution crisis [Sludge Oil] harm the island community? Evidence from the island of Bintan?". To answer this, a qualitative method is needed by analyzing the distribution of data on the internet and data from online news about the black oil pollution crisis harming the island community. The results of the study show that the black oil crisis [Sludge Oil] in the islands is very detrimental to the income of fishing communities, harms the ecosystem where the island community lives and harms tourism in the Bintan Islands. The implications of the black oil pollution crisis that occurred in the Bintan Islands are shown by the death of marine biota and pollution of mangrove forests, as well as the dirtiness of the sea and beaches due to the black oil waste. This research recommends intensifying central and regional surveillance of international sea lanes to detect criminals on ships intentionally dumping sludge oil. Keywords: Crisis, Sludge Oil Pollution, Harm to Island Communities.